Ester-functionalized, wide-bandgap derivatives of PM7 for simultaneous enhancement of photovoltaic performance and mechanical robustness of all-polymer solar cells. Issue 5 (14th January 2021) - You, Hoseon; Jones, Austin L.; Ma, Boo Soo; Kim, Geon-U; Lee, Seungjin; Lee, Jin-Woo; Kang, Hyunbum; Kim, Taek-Soo; Reynolds, John R.; Kim, Bumjoon J.
Abstract : Photovoltaic performance and mechanical robustness of all-polymer solar cells are simultaneously enhanced by developing ester-functionalized, wide-bandgap PM7 derivatives. Abstract : In this study, two wide-bandgap PM7 polymer derivatives are developed via simple structural modification of the fused-accepting unit by incorporating ester groups on terthiophene at different positions ( i.e., two ester groups on the outer thiophenes (PM7 D1) and on the central thiophene (PM7 D2)). This simple modification creates a higher-energy light absorption window, providing better complementary light harvesting with naphthalenediimide-based acceptor, P(NDI2HD-Se). As a result, PM7 D1-based all-polymer solar cells (all-PSCs) exhibit a high power conversion efficiency (PCE) of 9.13%, which outperforms that of the PM7-based all-PSC (PCE = 6.93%). Importantly, the ester structural modification has significant impact on the thin-film mechanical ductility and robustness. For example, elongation properties of PM7 D1 and PM7 D2 pristine films are significantly improved by ca. 2.5 times compared to that of PM7. This result is attributed to the flexible ester groups, which are able to effectively compensate for applied stress. The improved ductile properties of PM7 D1 and PM7 D2 also affect the mechanical ductility of the blend films, leading to 1.5-fold increase in crack onset strain compared with that of the PM7 blend film. Therefore, we demonstrate that the introduction of ester groups in conjugated polymers provides a simple and promising strategy for future stretchable electronics.